Analisis Kualitatif Pengaruh Cyberloafing pada Karyawan Work From Home pada Masa Pandemi Covid-19 - Afifah Khairunnisa; Diah Priharsari; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Covid-19 pandemic has pushed companies to change the way they work from the office to work from home (WFH). The WFH policy requires companies to maximize the use of technology to carry out WFH properly. This poses its own challenges. the use of technology during WFH can eliminate working hours restrictions and increase the use of social media during working hours which is known as cyberloafing behavior. Cyberloafing is the activity of surfing on the internet for personal purposes. Based on previous research, cyberloafing can have positive and negative impacts on employees. The purpose of this research is to carry out an analysis process regarding how employees work during WFH during the Covid-19 pandemic and to record further about cyberloafing activities and their impacts. The results of the study show that the WFH policy is still changing frequently and has an impact on the adjustment of the way employees work. In addition, cyberloafing activities that are often carried out by employees are accessing social media, listening to digital music, making video calls with friends, and watching streaming videos. The impacts felt by employees are feeling better prepared to work, more focused, and increasing productivity.